Brief comments on the mechanisms implemented by Senace for the effective citizen participation within the environmental certification process - Queirolo Romero, Ana Paula (2019)
Several mining extraction projects have been carried out disregarding the right of citizen participation of whom are aff ected by them.Factors such as gender or cultural gaps prevent its effective exercise. Therefore, to guarantee the right of citizen environmental participation, SENACE has incorporated Gender and Intercultural approaches to their environment assessment procedure.In this article, the author stars to review the concept of citizen participation and then analyze its environmental variant. Later, analyzes the recognition and implications of citizen environmental participation within the context of environmental assessments, to further evaluate the need of incorporating the Gender and Intercultural approaches. Finally, analyzes the role of the State as a guarantor of the right of citizen participation and values the incorporation of these approaches made by SENACE.